Obstacles to ethical decision-making : mental models, Milgram and the problem of obedience - Werhane, Patricia Hogue (Cambridge University Press, 2013)
"In commerce, many moral failures are due to narrow mindsets that preclude taking into account the moral dimensions of a decision or action. In turn, sometimes these mindsets are caused by failing to question managerial decisions from a moral point of view, because of a perceived authority of management. In the 1960s, Stanley Milgram conducted controversial experiments to investigate just how far obedience to an authority figure could subvert his subjects' moral beliefs. In this thought-provoking work, the authors examine the prevalence of narrow mental models and the phenomenon of obedience to an authority to analyse and understand the challenges which business professionals encounter in making ethical decisions. Obstacles to Ethical Decision-Making proposes processes - including collaborative input and critique - by which individuals may reduce or overcome these challenges. It provides decision-makers at all levels in an organisation with the means to place ethical considerations at the heart of managerial decision-making"--